2007
DOI: 10.1080/00016340600935730
|View full text |Cite
|
Sign up to set email alerts
|

Cervical phIGFBP‐1 in the evaluation of the risk of preterm delivery

Abstract: The phosphorylated isoform of insulin-like growth factor binding protein-1 in cervical secretions is a potential specific marker for preterm delivery occurring before 37 weeks. This test may have an important role in the management of women presenting with symptoms suggestive of preterm labour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 24 publications
2
24
1
1
Order By: Relevance
“…Kekki et al [17] also discussed the high negative predictive value of determining IGFBP-1, and Bittar [18] also tested pregnant women without symptoms of preterm delivery and found that the sensitivity of the test was 83%, positive predictive value 63%, specificity 80%, and negative predictive value 92%. Similar results of high specificity and negative predictive value in asymptomatic pregnant women were shown in other studies published last year [19,20,21,22].…”
Section: Discussionsupporting
confidence: 91%
“…Kekki et al [17] also discussed the high negative predictive value of determining IGFBP-1, and Bittar [18] also tested pregnant women without symptoms of preterm delivery and found that the sensitivity of the test was 83%, positive predictive value 63%, specificity 80%, and negative predictive value 92%. Similar results of high specificity and negative predictive value in asymptomatic pregnant women were shown in other studies published last year [19,20,21,22].…”
Section: Discussionsupporting
confidence: 91%
“…146,150 Otherwise all studies used cohorts of pregnant women; all except two 151,152 reported prospective data collection design and, with one exception, 151 had provided adequate test description. The methodological quality of the included primary studies is summarised in Figure 18.…”
Section: Study Characteristics and Qualitymentioning
confidence: 99%
“…Nine studies provided data on cervicovaginal phosphorylated insulin-like growth factor binding protein-1 (phI-GFBP-1), [65][66][67]69,[72][73][74]77,79 seven studies provided data on relaxin, 34,60,61,70,71,75,78 three studies provided data on cervicovaginal human chorionic gonadotrophin (hCG), 63,68,76 two studies provided data on cervicovaginal prolactin, 62,64 four studies provided data on pregnancy-associated plasma protein-A (PAPP-A), 81,84,85,87 two studies provided data on activin-A, 80,82 and one study each provided data on placental protein-13 (PP13) 83 and pregnancy-specific-b1 glycoprotein (SP1). 86 For cervicovaginal levels of hCG, phIGFBP-1, and prolactin, the pooled sensitivities, specificities, positive and negative LRs to predict preterm birth before 32, 34, and 37 weeks of gestation ranged between 33 and 83% (median, 67%), 62 and 97% (median, 79%), 1.6 and 19.0 (median, 3.2), and 0.2 and 0.8 (median, 0.5), respectively (Table 1).…”
Section: Placental Protein/hormone-related Biomarkersmentioning
confidence: 99%